Impediments To Establishing Somalia’s Judicial Service Commission : Challenges & Future Prospects - Bashir Yusuf Adan (International Journal of Law Policy and Governance, 2026)
Judicial councils are institutional mechanisms designed to insulate the appointment, promotion, and discipline of judges from partisan political influence while ensuring accountability within the judiciary. Positioned between two extremes self-perpetuating judicial control and complete political dominance these bodies are central to safeguarding judicial independence and enhancing the rule of law. The establishment of a Judicial Service Commission (JSC) is thus a critical reform in strengthening the administration of justice in any state. In Somalia, the Higher Judicial Council traces its origins to 1956 under the Italian Trusteeship administration. Its current constitutional mandate, however, is enshrined in the Provisional Constitution adopted in 2012. Despite this formal recognition, operationalization has been hindered by legal, institutional, and political impediments. This study examines the historical evolution of judicial governance in Somalia, identifies the principal barriers to establishing a functional JSC, and evaluates comparative models from other jurisdictions. Drawing on a qualitative methodology, including semi-structured interviews with key stakeholders, the research provides an evidence-based analysis of both the challenges and the reform opportunities. The paper concludes by proposing a contextually appropriate commission structure aligned with Somalia’s constitutional vision and its broader objectives for judicial reform and democratic governance.